Transformações socioespaciais na aglomeração urbana de Paris : princípios interpretativos e o léxico conceitual na compreensão da produção do espaço - Juliana Nazaré Luquez Viana (Confins)
The research developed at the University of Paris-Sorbonne IV, under the supervision of Professor Emeritus Paul Claval, sought to analyze and discuss the uses and meanings of concepts that aim to express the socio-spatial transformations through which the city is passing, as well as to perceive the conceptual approach and the methodological perspective for understanding contemporary urban reality. Our interest in combining the theoretical approach and the methodological perspective for the construction of conceptual frameworks, seeking to clarify socio-spatial transformations in the context of urbanization as a historical process, was to perceive the different rhythms of achievement. Our main objective revolved around the necessary discussion about the concepts that reveal the nature and meanders of the dynamics of socio-spatial transformations, of a metropolitan nature.